Longevity Factor FOXO3: A Key Regulator in Aging-Related Vascular Diseases - Zhao, Yan; Liu, You-Shuo (Frontiers in Cardiovascular Medicine, 2021)
Forkhead box O3 (FOXO3) has been proposed as a homeostasis regulator, capable of integrating multiple upstream signaling pathways that are sensitive to environmental changes and counteracting their adverse effects due to external changes, such as oxidative stress, metabolic stress and growth factor deprivation. FOXO3 polymorphisms are associated with extreme human longevity. Intriguingly, longevity-associated single nucleotide polymorphisms (SNPs) in human FOXO3 correlate with lower-than-average morbidity from cardiovascular diseases in long-lived people. Emerging evidence indicates that FOXO3 plays a critical role in vascular aging. FOXO3 inactivation is implicated in several aging-related vascular diseases. In experimental studies, FOXO3-engineered human ESC-derived vascular cells improve vascular homeostasis and delay vascular aging. The purpose of this review is to explore how FOXO3 regulates vascular aging and its crucial role in aging-related vascular diseases.